Current approaches for the regeneration and reconstruction of ocular surface in dry eye - Singh, Vimal Kishor; Sharma, Pallavi; Vaksh, Uttkarsh Kumar Sharma; Chandra, Ramesh (Frontiers in Medicine, 2022)
Significant research revealed the preocular tear film composition and regulations that remain vital for the maintenance of Ocular surface functional integrity. Inflammation triggered by many factors is the hallmark of Ocular surface disorders or dry eyes syndrome (DES). The tear deficiencies may lead to ocular surface desiccation, corneal ulceration and/or perforation, higher rates of infectious disease, as well as the risk of severe visual impairment and blindness. Clinical management remains largely supportive, and palliative and a frequent, lifelong use of different lubricating agents. Few advancements such as punctual plugs, non-steroidal anti-inflammatory drugs, salivary gland autograft are of limited use. Recently, cell-based therapies, tissue engineering, and regenerative medicine have evolved as a long-term cure for many diseases including ophthalmic diseases. The present article focuses on the different regenerative medicine and reconstruction/ bioengineered lacrimal gland formation strategies reported so far along with their limiting factors and feasibility as an effective cure in the future.